Rubix cube and kaleidoscope-an interesting tool for anxiety management in children - Velu, Tejaswini; Bhayya, Deepak P.; Jai Krishna, Aparna; Krishnadasan, Amritha (International Journal of Contemporary Pediatrics, 2024)
Background: Dental anxiety is a common fear for children undergoing dental treatments. Distraction involves diverting children’s attention away from painful stimuli during invasive dental procedures and is the most effective when tailored to child’s developmental level. Parents prefer non-invasive techniques over general anaesthesia, sedation, restraint, and hand over mouth. Introducing distraction aids using Rubix cube or kaleidoscope can help in the reduction of dental anxiety during the dental visits. The objective of this study was to compare Rubix cube and kaleidoscope as tools for reducing dental anxiety during the treatment. Methods: Randomized clinical trial was conducted among 60 children (5-12 years old). They were randomly divided into three groups (20 each): Group A (control group-did not receive anything), group B (received Rubix cube during treatment) and group C (received kaleidoscope during treatment). Chotta Bheem-Chutki scale was recorded prior to the appointment and after the dental treatment. This study demonstrated that patients subjected to Rubix cube and kaleidoscope therapy had a statistically significant reduction in anxiety compared to the control group after the dental treatment. Results: This study demonstrated that patients subjected to Rubix cube and kaleidoscope therapy had a statistically significant reduction in anxiety compared to the control group after the dental treatment. Conclusions: Distraction aids like Rubix cube and kaleidoscope during the dental procedure plays an important role in managing dental anxiety in children and can be effectively incorporated into routine clinical practice.